Steel fiber reinforced concrete: A review of its material properties and usage in tunnel lining. (December 2021) - Wang, Xiuling; Fan, Feifei; Lai, Jinxing; Xie, Yongli
Highlights: Studies on the composition and typical properties of SFRC are systematically reviewed. Problems and challenges of mesh-reinforced linings and usage of SFRC in tunnel linings. Advantages, design considerations and practical performance of SFRC linings are discussed. Abstract: The complicated tunnelling conditions and variable engineering demands have made numerous challenges of mesh-reinforced lining structures. Thereafter, the steel fiber reinforced concrete (SFRC) is said to be a reliable alternative to mesh-reinforced linings. This paper reviews the constituent materials and typical properties of SFRC. The main causes of mesh-reinforced lining cracks or structure failures are summarized, and current challenges for mesh-reinforced linings are examined. Also, the advantages of using SFRC for the realization of the tunnel linings are highlighted. Furthermore, design considerations and some practical cases on application performance of SFRC in tunnel linings are summarized. This review confirmed the positive effect of SFRC lining on rock displacement control, lining pressure reduction, and global and local stability of the support structures. The research provides solid insights for promoting the development of SFRC in tunnel linings.